STRATEGY TO IMPROVE RICE SEEDS BASED ON SOCIAL CAPITAL IN PANGKEP DISTRICTSOUTH SULAWESI - A Iva Mundiyah; Rahmawati Tahir (AGROLAND: The Agricultural Sciences Journal, 2019)
This study analyzed the roles of social capital in rice breeding at Kassiloe village of La’bakkang Subdistrict,Pangkep Districtand provided recommendations on strategies to strengthen social capital based on informal institutions that can be applied or implemented by farmers groups. Data were solicited through face to face interviews and focus group discussion (FGD) to farmers and rice seed breeding practitioners. Qualitative and quantitative SWOT analyses were performed to determine the best strategy to improve rice seeds at the study site. Based on the research findings, a strategy was developed (Strengths - Threats) to improve extension agents’ creativity to motivate farmers, enhance farmers groups meeting to utilize certified seeds. Strategy (Weakness – Threats) to centralize trainings using demplot seeds from the breeding sites, the use of efficient alsintan and application of modern agriculture technologies. Strategy (Strengths – Opportunities) to enhance communication and groups’ meetings to widen the demplot using seeds from the breeding activities, continued planting schedule synchronization and strategy (Weakness – Opportunity) to agree on the selling price of the bred seeds so that all the groups’ members can get some profit, massive and measured agriculture technologies applicationin order to give equal profit to all group members.